THE VALIDITY AND RELIABILITY STUDIES OF TURKISH VERSION OF THE ACADEMIC MAJORS SATISFACTION SCALE - Şule ODABAŞI (Fırat University, 2019)
The aim of the present study is to examine the validity and reliability of the Turkish Version of the Academic Majors Scale (Nauta, 2007). Participants were 302 university students. Primarily the Academic Majors Satisfaction Scale was translated into Turkish. The Turkish form was back-translated into English and the consistency between the Turkish and English forms was examined. Finally they discussed the Turkish form and along with some corrections the scale was prepared for validity and reliability analyses. Academic Majors Satisfaction Scale was used as data collecting method in the research. The scale contains 6 items (e.g., “I feel good about the major I’ve selected.”) with each item rated on a 5-point Likert-type scale. Participants voluntarily participated in research. Completion of the scales was anonymous and there was a guarantee of confidentiality. The scales were administered to the students in groups in the classrooms. Prior to administration of measures, all participants were told about purposes of the study. In this study, confirmatory factor analysis (CFA) was executed to confirm the original scale’s structure in Turkish culture. As reliability analysis Cronbach alpha internal consistency coefficients and the item-total correlations were calculated. Data were analyzed using LISREL 8.54 and SPSS 20.0 package programs. CFA provide empirical-based evidence for determining whether the Turkish version of Academic Majors Satisfaction Scale would yield or construct a similar structure to the original version of Academic Majors Satisfaction Scale. Results of confirmatory factor analysis demonstrated that the six items yielded one factor and the uni-dimensional model was well fit (x²= 4.61, df= 8, RMSEA= 0.000, CFI= 1.00, IFI= 1.00, SRMR= .015). Cronbach alpha internal consistency reliability coefficient was .86 for scale. Corrected item-total correlations ranged from .45 to .77. These findings demonstrate that this scale is a valid and reliable instrument.